Characterization of novel polydiacetylene gel dosimeter for radiotherapy. (24th August 2020) - Walg, Y Peleg; Silveira, M A; Eafergan, N; Krutman, Y; Baffa, O; Berman, A; Orion, I
Abstract: Polymer gel dosimeters are instrumental for clinical and research applications in radiotherapy. These dosimeters possess the unique ability to record dose distribution in three dimensions. A Polymer gel dosimeter is composed of organic molecules in a gel matrix, which upon irradiation polymerize to form a conjugated polymer with optical absorbance proportional to the irradiated dose. Other required characteristics of a radiotherapy clinical dosimeter are soft-tissue equivalency, linear dose-response in a range of clinical treatments, and long term stability for the duration of the analysis. The dosimeter presented in this paper is based on diacetylene bearing fatty acid aggregates embedded in a soft-tissue equivalent gel matrix, Phytagel™, which upon irradiation polymerize to form a blue phase polydiacetylene with a strong optical absorption. Initial characterization showed that PDA-gel irradiated with 160 kV x-ray responded linearly to the irradiated dose, and the calculated diffusion coefficient is 6 · 10 − 3 mm 2 Hr what is very low. It was also found that the percentage depth dose (PDD) curve of the PDA-gel in a 4 × 4 cm 2 field, irradiated with 6 MV x-rays, was with good agreement with the literature. PDA-gel has the potential to detect absorbed dose in a range of clinical radiological irradiation regimes.